SMARCB1/INI1-deficient tumors of adulthood - Parker, Nathaniel A. (F1000Res, 2020)
The SMARCB1/INI1 gene was first discovered in the mid-1990s, and since then it has been revealed that loss of function mutations in this gene result in aggressive rhabdoid tumors. Recently, the term “rhabdoid tumor” has become synonymous with decreased SMARCB1/INI1 expression. When genetic aberrations in the SMARCB1/INI1 gene occur, the result can cause complete loss of expression, decreased expression, and mosaic expression. Although SMARCB1/INI1-deficient tumors are predominantly sarcomas, this is a diverse group of tumors with mixed phenotypes, which can often make the diagnosis challenging. Prognosis for these aggressive tumors is often poor. Moreover, refractory and relapsing progressive disease is common. As a result, accurate and timely diagnosis is imperative. Despite the SMARCB1/INI1 gene itself and its implications in tumorigenesis being discovered over two decades ago, there is a paucity of rhabdoid tumor cases reported in the literature that detail SMARCB1/INI1 expression. Much work remains if we hope to provide additional therapeutic strategies for patients with aggressive SMARCB1/INI1-deficient tumors.